Mountain-wave induced polar stratospheric clouds and their representation in the global chemistry model ICON-ART - Weimer, Michael; Buchmüller, Jennifer; Hoffmann, Lars; Kirner, Ole; Luo, Beiping; Ruhnke, Roland; Steiner, Michael; Tritscher, Ines; Braesicke, Peter (2020)
Polar stratospheric clouds (PSCs) are a driver for ozone depletion in the lower polar stratosphere. They provide surfaces for heterogeneous reactions activating chlorine and bromine reservoir species during the polar night. PSCs are represented in current global chemistry-climate models, but one process is still a challenge: the representation of PSCs formed locally in conjunction with unresolved mountain waves. In this study, we present simulations with the ICOsahedral Nonhydrostatic modelling framework (ICON) with its extension for Aerosols and Reactive Trace gases (ART) that include local grid refinements (nesting) with two-way interaction. Here, the nesting is set up around the Antarctic Peninsula which is a well-known hot spot for the generation of mountain waves in the southern hemisphere. We compare our model results with satellite measurements from the Cloud-Aerosol LIdar with Orthogonal Polarisation (CALIOP) and the Atmospheric InfraRed Sounder (AIRS). We study a mountain wave event that took place from 19 to 29 July 2008 and find similar structures of PSCs as well as a fairly realistic development of the mountain wave in the Antarctic Peninsula nest. We compare a global simulation without nesting with the nested configuration to show the benefit. Although the mountain waves cannot be resolved adequately in the used global resolution (about 160 km), their effect from the nested regions (about 80 and 40 km) on the global domain is represented. Thus, we show in this study that by using the two-way nesting technique the gap between directly resolved mountain-wave induced PSCs and their representation and effect on chemistry in coarse global resolutions can be bridged by the ICON-ART model.